Evaluation of efficiency, effectiveness and social equity of the property tax in the municipality of Sogamoso, based on the last cadastral update - Izaquita-Orduz, Juan Sebastián; Bernal-Burgos, Rigoberto Antonio (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2013)
This research project was based on the assessment of the levels of efficiency, effectiveness and socialequity of the tax collection process on property in the city of Sogamoso, based on the last cadastral update. Basically, it was established the amount caused by this tax before the last cadastral update and was compared with the actual amount in the same period, as well as the resources used to achieve the collection of each fiscal year. The result of this comparison broadly determined that the level of effectiveness is satisfactory in terms of money but it was not in terms of number of properties, and that the efficiency of the collection process was greatly encouraging. In terms of meters built since last cadastral update, it was established its evolution between each cadastral update. In addition, it was analyzed the social equity component which involves the collection of property tax, and which was an important element in determining the degree of efficiency and effectiveness that was intended to establish. Besides showing the evolution of the collection, this project presents results that will be decisive in action and budget execution plans for the current tax administration in general and for property tax in particular.